2012
DOI: 10.1093/cid/cis286
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose, Extended-Interval Colistin Administration in Critically Ill Patients: Is This the Right Dosing Strategy? A Preliminary Study

Abstract: In critically ill patients with otherwise untreatable nosocomial infection due to gram-negative bacteria susceptible only to colistin, a high-dose, extended-interval colistin dosing regimen is, according to the pharmacokinetic/pharmacodynamic behavior of the drug, associated with low renal toxicity and high efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
180
5
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(209 citation statements)
references
References 37 publications
(60 reference statements)
9
180
5
9
Order By: Relevance
“…intravenous polymyxins alone in MDR GNB infections, most of which were pneumonias. It's indicated that the mortality ranged from 0% to 74.3% (4,21,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), clinical response (cure and improvement) rate 7-82.1%, and microbiological eradication 27.3-73.9% (24,(33)(34)(35)(36)(37)(38). In respect to the colistin only susceptible strains, it's reported that the mortality in hospitals of intravenous colistin monotherapy was 50% (16/32) (Figure 2), 11 patients died in Intensive Care Unit (ICU) (39), and clinical cure was obtained in 82.1% of infectious episodes (23/28) and bacteriological clearance was achieved in 73.9% (17/23) of the cured infectious episodes (38).…”
Section: Combination Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…intravenous polymyxins alone in MDR GNB infections, most of which were pneumonias. It's indicated that the mortality ranged from 0% to 74.3% (4,21,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), clinical response (cure and improvement) rate 7-82.1%, and microbiological eradication 27.3-73.9% (24,(33)(34)(35)(36)(37)(38). In respect to the colistin only susceptible strains, it's reported that the mortality in hospitals of intravenous colistin monotherapy was 50% (16/32) (Figure 2), 11 patients died in Intensive Care Unit (ICU) (39), and clinical cure was obtained in 82.1% of infectious episodes (23/28) and bacteriological clearance was achieved in 73.9% (17/23) of the cured infectious episodes (38).…”
Section: Combination Therapymentioning
confidence: 99%
“…Toxicities associated with colistin do not appear to increase with use of a loading dose (38,46). Limited clinical evidence is available.…”
Section: Loading Dosesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, extended dosing intervals may lead to periods of low colistin concentrations allowing for resistant subpopulations to occur within a microbial population susceptible to colistin (heteroresistance). [28][29][30]34] Small, uncontrolled studies report good efficacy, without significant renal toxicity, of high-dose CMS regimens given 12-hourly [35] or daily. [31] There are no randomised, controlled, clinical trials (RCTs) evaluating the efficacy and safety of once-, twice-and thrice-daily dosing of colistin.…”
Section: Dosing Intervalmentioning
confidence: 99%
“…3,45,47,63 A recently-published prospective observational study in intensive care unit patients with severe infections due to Gram-negative bacteria susceptible only to colistin recorded clinical cures in 82% of cases when colistin was administered as a 9-million-unit loading dose followed by 9 million units daily, given in two doses, as maintenance therapy. 64 Combination of colistin/polymyxin B with other agents to which the bacteria show in vitro sensitivity is strongly encouraged (e.g. with aminoglycosides and/or tigecycline for the treatment of infections due to Klebsiella pneumoniae with KPC carbapenemases).…”
mentioning
confidence: 99%